(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
As we all know that rice is the most consumed food by everyone in our day-to-day life. In rice manufacturing industries the market demand always depends on the quality of rice. In verifying the rice quality, the physical dimensions like length, width and thickness plays a crucial role. Normal methods used for detection of these factors are time consuming, and not accurate as they are performed manually. This problem had given the way for development of computerized vision in rice quality detection. In the proposed method both image processing and machine learning techniques are clubbed to analyse and grade the quality of rice kernels with the help of classifiers in python platform.